Metode Pembobotan Simplified Pivot Pairwise Relative Criteria Importance Assessment dan COPRAS Dalam Penentuan Seleksi Penerimaan Guru - Heri Bambang Santoso (PT. Tech Cart Press, 2023)
Teacher recruitment selection is a crucial process in ensuring that the education provided to the younger generation is delivered by qualified and competent individuals. Teacher recruitment selection has a strategic role in shaping the future of education by selecting individuals who are able to have a positive impact on students' intellectual development and character. The selection of teachers carried out through the integration of PIPRECIA-S and COPRAS is expected to improve the quality of education by placing individuals who have qualifications, abilities, and dedication in accordance with educational needs. The ranking results using the PIPRECIA-S and COPRAS methods showed that candidates on behalf of Syafira Putri got first place with a final score of 100%, candidates on behalf of Jelita got second place with a final score of 99.58%, candidates on behalf of Rahmadi got third place with a final score of 96.42%.